(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The stratigraphic succession of central Dolpo (Tarap-Atali area) begins with thick calcsilicate marbles of inferred Cambrol-Ordovician age, injected by pegmatitic dykes. The strongly deformed mid-Paleozoic sequence comprises fossiliferous marls, dolomitic quartzarenites and dolomites. The latter are unconformably followed by earliest Late Devonian biocalcarenites, capped by a maior ironstone layer. The overlying offshore black pelites contain quanzose sandstones and bioclastic limestones at several intervals, indicating deposition in shelfal environments at latest Devonian times. The Carboniferous is poorly represented in the surveyed area. A major disconformity, cutting deep into Early? Carboniferous fenestellid-rich biocalcarenites at Tarap, is overlain by white quartzarenites interbedded with dark pelites, sharply followed by a fossiliferous marker horizon yielding a large brachiopod fauna of mid-Permian age (Costiferina arenites); the overlying fossiliferous shelfal pelites are unconformably followed by coarsening-upward quartzarenite sequences deposited in estuarine environments (Thini Chu Formation). In the Late Permian, another disconformity is overlain by conglomeratic to glauconitic arenites and shelfal pelites (Kuling Formation). The Triassic Tamba Kurkur Formation, with dolomitic subarkoses ar the base, consists of two condensed pelagic carbonate horizons of Dienerian and Smithian age, separated by dark pelites. Marly limestones and marls were deposited from the Spathian through the Carnian (Mukut Formation), and are overlain by the thick Tarap Shale. A thin basal condensed bed is followed by dark pelites yielding Early Norian ammonoids, by thick siltstones with phosphatic nodules and next by dark shales and calcareous siltstones with large Zoophycos-type burrows. The upper part of the unit contains up to fine-grained quartzo-feldspathic sandstones, nodular marly limestones and ironstone horizons ("upper assemblage"). The Late Triassic shallowing- upward succession is capped by dolomitic and oolitic quartzarenites with spectacular herringbone structures (Quartzite Series). The largely Lower Jurassic shallow-water Kioto Limestone, still containing metric intervals of up to medium-grained hybrid quartzarenites in the lower part, is followed by Middle Jurassic lumachelles (Laptal Formation). Younger terms of the succession are not exposed in Dolpo.